STRATEGI GURU DALAM MENGATASI SISWA LAMBAT BELAJAR PADA PELAJARAN MATEMATIKA DI KELAS V - Farzana Munawwarah; Eko Kuntarto; Andi Gusmaulia Eka Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This qualitative research aims to describe the strategies employed by teachers in addressing slow learners in mathematics subjects. The research subjects consisted of teachers and students at SD Negeri 116/IV Kota Jambi. The study was conducted from March to April 2025. Data were collected through observation, student questionnaires, and interviews with classroom teachers. The findings revealed that slow learners exhibit certain characteristics, such as limited cognitive capacity, low memory retention, difficulty concentrating, and challenges in expressing ideas verbally. To address these issues, teachers implemented several strategies, including simplifying instructional materials, using concrete teaching aids, regularly repeating lessons, and creating a conducive learning environment. In addition, teachers provided positive reinforcement to boost students’ self-confidence. These findings are expected to serve as a reference for educators in designing appropriate instructional strategies for students with diverse learning needs and to contribute to further research in the field of elementary education.